Theoretical Aspects of Migration and its Impact on Political Processes - Igonin, Denis Ivanovich; Garipov, Ruslan Faritovich (International Journal of Criminology and Sociology, 2022)
The authors of the paper set the goal of examining the theoretical aspects of migration and showing the relationship between the influence of this social phenomenon on the political processes of the state and state policy in general. The authors highlight the main interdisciplinary approaches to the definition of the term “migration” with the aim of concretizing it in political science within the framework of the study. The study also answers the question of the relationship between "policy" and "politics" within a migration policy by comparing "state migration policy" and "migration policy", concerning which there is a different interpretation. The object of research is migration. The subject is migration policy and state migration policy. The topic is relevant because in the early 2000s migration acquired a new global scale under the influence of many heterogeneous factors often caused by adverse economic, social and socio-psychological conditions, as well as military conflicts of an interreligious and ethnopolitical nature. The research uses systemic, comparative, institutional, and ethnopolitical approaches. The systematization of approaches presents the scientific novelty to the definition of migration, as well as by the mutual influence of migration processes and political and administrative decisions.